'n Narratiewe teologiese verkenning van negatiewe koronêre vatomleidingsoperasieuitkomste: 'n chirurgiese hermeneutiek - M. J. Swart; G. J. van Zyl; J. A. van den Berg (Acta Theologica)
Negative outcomes of coronary bypass operations not only have an important impact on the patient and family, but also have an influence on the cardiac surgeon on many levels. Within a specific surgical context and from a tradition of faith, interwoven narratives present the possibility of an interdisciplinary conversation between medical science and theology. By following an auto-ethnographic approach, an invitation is offered to participate in sharing the surgeon’s database as a new hermeneutic text. Fellow cardiac surgeons on a national level are involved by way of a Delphi research model, providing for a collective tracing of God’s involvement in surgical outcomes. In a process of a reinterpretation of negative surgical outcomes, Henri Nouwen’s three poles of a spiritual movement can lead to spiritual transformation. Bearing physiological barriers and lifestyles in mind, as well as God’s involvement, the patient and surgeon can in a new manner reflect on possible negative outcomes following operative procedures.